2016
DOI: 10.1016/j.jhsa.2016.07.054
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Analysis of Time to Surgery and Travel Distances for Brachial Plexus Surgery

Abstract: Purpose Despite the importance of timely evaluation for patients with brachial plexus injuries (BPI), in clinical practice we have noted delays in referral. Because the published BPI experience is largely from individual centers, we used a population-based approach to evaluate the delivery of care for patients with BPI. Methods We used statewide administrative databases from Florida (2007–2013), New York (2008–2012) and North Carolina (2009–2010) to create a cohort of patients who underwent surgery for BPI (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Thus, uninsured patients, government-insured patients, and those patients with claims covered by automotive insurance, who may represent a substantial portion of BPI patients, were not included in this study. A prior study using administrative data reported that 47% of BPI patients have private insurance 34 ; our exclusion of BPI patients without private insurance limits the generalizability of our findings to all BPI patients. While it would be ideal to examine claims from an all-payer database, currently-available national datasets (such as those from Health Care Utilization Project [HCUP] and Agency for Healthcare Research and Quality) are limited in their length of follow-up (National Inpatient Sample tracks only individual hospitalizations), states/years available (HCUP statewide databases are not available for all states and all years), and data type available (pharmacy claims are not available in other datasets).…”
Section: Discussionmentioning
confidence: 78%
“…Thus, uninsured patients, government-insured patients, and those patients with claims covered by automotive insurance, who may represent a substantial portion of BPI patients, were not included in this study. A prior study using administrative data reported that 47% of BPI patients have private insurance 34 ; our exclusion of BPI patients without private insurance limits the generalizability of our findings to all BPI patients. While it would be ideal to examine claims from an all-payer database, currently-available national datasets (such as those from Health Care Utilization Project [HCUP] and Agency for Healthcare Research and Quality) are limited in their length of follow-up (National Inpatient Sample tracks only individual hospitalizations), states/years available (HCUP statewide databases are not available for all states and all years), and data type available (pharmacy claims are not available in other datasets).…”
Section: Discussionmentioning
confidence: 78%
“…Even after successful surgical reconstruction, many individuals do not return to the same occupation or return to work at all after a BPI [4][5][6] . Furthermore, there are inefficiencies in care delivery for patients with BPI in the U.S., which may compromise clinical outcomes given the time-sensitive nature of the injury 7 . Estimation of the costs associated with BPI from a societal perspective would support continued allocation of resources for clinical care and research, with the ultimate goal of optimizing return to work and improving quality of life after a BPI.…”
mentioning
confidence: 99%
“…e80(7) TH E J O U R N A L O F B O N E & JOINT SURGERY d J B J S . O R G VOLUME 101-A d N U M B E R 16 d AUGUST 21, 2019INDIRECT COST O F TRAUMATIC BRACHIAL PLEXUS I N J U R I E S I N T H E U N I T E D S TAT E S…”
mentioning
confidence: 99%
“…This process is similar to strategies previously employed when identifying patients undergoing surgery for brachial plexus injury from administrative data sources. 7 , 8 We included patients regardless of the number of additional CPT-4 codes associated with them. Associated diagnostic codes for each patient were reviewed but were not used for case inclusion criteria owing to concerns for accuracy.…”
Section: Methodsmentioning
confidence: 99%